Pandan–vanilla rotation mitigates Fusarium wilt disease in vanilla: insights from rhizosphere microbial community shifts - Hong, Shan; Xing, Yizhang; Yang, Jinming; Zhao, Qingyun; Su, Fan; Zhuang, Huifa; Wang, Hui; Wu, Zhuangsheng; Chen, Yisong (Frontiers in Microbiology, 2025)
IntroductionVanilla monoculture often leads to Fusarium wilt disease, affecting the industry globally.MethodsHere, we evaluated the effects of vanilla–black pepper, –pandan, and –sweet rice tea rotations (i.e., growing vanilla in soil previously planted with these crops) on Fusarium oxysporum abundance and rhizosphere microbial communities using real-time quantitative PCR and high-throughput sequencing.ResultsPandan rotation, in particular, reduced disease incidence to 17% and decreased F. oxysporum copy numbers; sweet rice tea showed similar suppressive effects. Crop rotation significantly increased fungal diversity and richness. Different cropping systems, including fallow, monoculture and crop rotation, significantly influenced fungal and bacterial community development, with cropping system and rotated crops being the main drivers of rhizosphere community assembly. The black pepper and pandan rotations specifically enriched certain fungal OTUs, such as OTU1_Thermomyces, OTU37_Arthrobotrys, and OTU18_Arthrobotrys, which serve as biomarkers for the presence of F. oxysporum. After pandan rotation, microbial interactions within the rhizosphere intensified, with notable enrichment of core bacterial taxa, including OTU22_Nitrosospira, OTU56_Lacibacterium, and OTU178_Actinospica. Soil pH was identified as a significant factor influencing microbial community assembly. The fungal community structure, along with core OTU22_Nitrosospira and soil pH, was pivotal in curbing pathogen growth, explaining 25.19%, 8.61%, and 20.45% of the variance, respectively.ConclusionThis study revealed that incorporating pandan into crop rotation may effectively alleviate soil-borne diseases during vanilla production.